Lithium ion battery electrode material and preparation method thereof
Through the preparation of cubic selenide and carbon-based composite materials, the problem of volume change and poor conductivity of the negative electrode material of lithium-ion battery during charging and discharging is solved, and the high purity and excellent cycle stability of the material are achieved. It is suitable for new energy vehicles Battery.
Patent Information
- Application Number
- CN202411298174.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The volume change of transition metal selenide of the existing lithium-ion battery negative electrode material during charging and discharging leads to powdering of active substances, poor circulation life and stability of the material, and poor conductivity, affecting electron transfer.
A cubic carbon-based composite material composed of cubic selenide and carbon is stabilized by pretreatment and step-by-step selenization treatment of MOF material, soaking and carbonization process using a mixed aqueous solution of glucose and alkyl glycosides to stabilize the cubic structure and form a complete carbon Coating to reduce volume expansion and impurity generation.
It achieves uniform morphology, uniform size, excellent dispersion, high purity, improved conductivity and cycle stability of the material. It is suitable for the negative electrode materials of lithium-ion batteries of new energy vehicles, extending the cycle life and improving the battery life.
Smart Images

Figure CN119118071A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a lithium ion battery electrode material and a preparation method thereof. Background Art
[0002] With the development of social economy and the improvement of people's living standards, human demand for energy is increasing day by day, but the increasing depletion of resources such as fossil fuels has posed a direct threat to the energy security of global human beings. For this reason, the development of new energy industry has become one of the important strategies for countries to get rid of economic recession, create employment opportunities and seize the commanding heights of future development. Lithium-ion batteries stand out from many new energy sources due to their advantages such as high energy density, long cycle life and environmental friendliness, and are widely used in mobile electronic devices, new energy vehicles and other fields.
[0003] However, the negative electrode material of commercial lithium-ion batteries is usually graphite, but the theoretical capacity of graphite is only 372mAh / g, which cannot meet the needs of high-performance lithium-ion batteries. Therefore, people have carried out a series of studies on high-energy lithium-ion battery negative electrode materials, such as transition metal oxides, transition metal sulfides, transition metal selenides, etc. Compared with transition metal oxides and transition metal sulfides, transition metal selenides not only have high theoretical specific capacity, but also have low voltage platform and small polarization, and are a potential negative electrode material for lithium-ion batteries. However, during the charge and discharge process, transition metal selenides will undergo huge volume changes due to the insertion and extraction of lithium ions, thereby pulverizing the active material, causing the active material to separate from the current collector, resulting in capacity decay, and poor material cycle life and stability. In addition, the poor conductivity of transition metal selenides hinders the rapid transfer of electrons inside the active material.
[0004] At present, bimetallic selenides have attracted great attention as battery electrode materials due to their lower band gap and better conductivity compared to single metal selenides. However, the morphology and structure of bimetallic selenides have a significant impact on their electrochemical properties. For example, different structures of the same material, such as nanowires, nanosheets, nanotubes, and nanospheres, also exhibit significant differences in electrochemical properties. The lithium storage capacity and cycle stability of electrode materials have a decisive impact on their application in the automotive field, the endurance and stability of automotive performance. Summary of the invention
[0005] Based on the above technical problems, the present invention aims to provide a lithium-ion battery electrode material, specifically a cubic carbon-based composite material composed of cubic selenide and carbon.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned lithium-ion battery electrode material. The selenide carbon-based composite material prepared by the method has uniform morphology, excellent size uniformity, and excellent dispersibility. The carbon material forms a complete coating on the bimetallic selenide, effectively suppressing the volume expansion effect, and can be effectively applied to new energy vehicles as a negative electrode material for lithium-ion batteries of vehicles.
[0007] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a lithium-ion battery electrode material, characterized in that it includes preparing a MOF material, pretreating the MOF material and selenizing the MOF material, wherein the MOF material pretreating is to immerse the MOF material in a mixed aqueous solution of glucose and alkyl glycoside, keep the temperature at 70-90°C for 0.5-1h, and then dry it.
[0008] The mass percentage concentration of glucose in the mixed aqueous solution is 20-40%, and the mass ratio of glucose to alkyl glycoside is 4:0.5-1.
[0009] Furthermore, the selenization treatment is to place the pretreated MOF material and selenium powder in a tubular furnace, with the selenium powder at the upstream and the MOF material at the downstream, and heat to 400-450°C at a rate of 2-5°C / min under an argon atmosphere, and keep warm for 1.5-2.5 hours. During this process, the argon flow rate is 45-60 sccm, and then continue to heat to 550-600°C, and continue to keep warm for 0.5-1 hour. During this process, the argon flow rate is 30-40 sccm.
[0010] If the specific surface area of the electrode material is too small, the rate performance of the material is poor, and the cycle performance will also be poor. Therefore, increasing the specific surface area of the material to a certain extent is beneficial to improving the performance of the electrode material. The cubic structure of the bimetallic selenide composite material has a high specific surface area, which can effectively improve the electrochemical performance of the material. However, since the cubic structure of the MOF material has both planes and edges, it is difficult to ensure the stability of its cubic structure during the high-temperature selenization process. During the selenization process, the organic ligand is easily carbonized, resulting in the collapse of the cubic structure, and it is easy to agglomerate itself, and the final morphology is damaged and irregular. The formed carbon material is also difficult to completely wrap the bimetallic selenide formed by selenization. When the prepared material is used as an electrode material, it will face a serious volume expansion effect during the charge and discharge process, resulting in a decrease in the electrochemical performance of the material, such as the cycle stability and service life. In addition, some metal compound impurities other than MoSe2 and CoSe2 are easily produced during the selenization process, and the purity is low, resulting in the material performance not meeting expectations.
[0011] The cubic MnCo-MOF material prepared in the present invention is pre-treated by heating and soaking a mixed aqueous solution of high-concentration glucose and alkyl glycoside before selenization, and then undergoes step-by-step selenization treatment. During the soaking process, under the action of alkyl glycoside and heating, glucose slowly penetrates into the interior of the MnCo-MOF material. During the subsequent selenization, the alkyl glycoside and glucose that penetrate into the interior of the MnCo-MOF material simultaneously change the interface properties of the MnCo-MOF material, stabilize the template effect of the MnCo-MOF material, and effectively inhibit the problems of structural rupture, collapse, and agglomeration during the selenization process. While the alkyl carbon sugar and glucose are carbonized, a mutual traction force is generated between them and the organic ligand, inducing them to be evenly coated on the surface of the bimetallic selenide during the carbonization process to form a complete coating.
[0012] During the selenization treatment, the present invention performs the first step of selenization at 400-450° C. and then performs the second step of selenization at 550-600° C. During the two-step selenization process, the argon gas flow rate is adjusted to control the selenization process, thereby effectively reducing the generation of impurities during the selenization process. At the same time, under the above-mentioned selenization treatment, the interaction between the alkyl glycoside, glucose and the organic ligand during the carbonization process is adjusted, thereby improving the coating integrity of the carbon material on the metal selenide.
[0013] In the above cubic bimetallic selenides, Mn-based selenides can react to produce a variety of intermediate manganese ions to form different intermediate phases, and Co-based selenides react with Li in the battery. + An alloying reaction occurs, and the two metal elements provide more reactive sites through the reaction, thereby increasing the lithium storage performance. In the cubic structure, they act as buffer matrices for each other, effectively alleviating the volume effect caused by charging and discharging. The carbon layer uniformly and completely coated on the surface combined with the specific cubic structure further reduces the volume expansion and improves the conductivity of the material, showing excellent lithium ion cycle stability. These properties optimize the electrochemical performance of lithium ion batteries when the material is used as an electrode material for lithium ion batteries of new energy vehicles, thereby effectively improving the endurance and stability of new energy vehicles.
[0014] Furthermore, the MOF material is prepared by dissolving Mn(CH3COO)2·4H2O and PVP-K30 in a mixed solvent consisting of anhydrous ethanol and deionized water to obtain solution A, dissolving K3Co(CN)6 in deionized water to obtain solution B, and mixing solution A and solution B and aging at room temperature to obtain MnCo-MOF material.
[0015] Furthermore, in the solution A, the mass ratio of Mn(CH3COO)2·4H2O and PVP-K30 is 0.22~0.44:0.75~3, the mass volume ratio of Mn(CH3COO)2·4H2O and the mixed solvent is 0.1~0.5:100, in g / mL, and the volume ratio of anhydrous ethanol to deionized water is 2:1.
[0016] Furthermore, in the solution B, the mass volume ratio of K3Co(CN)6 and deionized water is 0.13~0.68:100, in g / mL.
[0017] Furthermore, the above solution A and solution B are mixed in a molar ratio of Mn to Co of 1.2 to 1.8:1 and aged at room temperature for 15 to 26 hours.
[0018] Most specifically, a method for preparing a lithium-ion battery electrode material is characterized by comprising the following steps: (1) Synthesis of MnCo-MOF materials Mn(CH3COO)2·4H2O and PVP-K30 were dissolved in a mixed solvent consisting of anhydrous ethanol and deionized water to obtain solution A, and K3Co(CN)6 was dissolved in deionized water to obtain solution B. Solution A and solution B were mixed according to a molar ratio of Mn to Co of 1.2 to 1.8:1, aged at room temperature for 15 to 26 hours, and the precipitate was collected by centrifugation, washed with ethanol and deionized water in turn, and then dried to obtain MnCo-MOF. In the solution A, The mass ratio of Mn(CH3COO)2·4H2O to PVP-K30 is 0.22~0.44:0.75~3, the mass volume ratio of Mn(CH3COO)2·4H2O to the mixed solvent is 0.1~0.5:100, in g / mL, the volume ratio of anhydrous ethanol to deionized water is 2:1, and in the solution B, the mass volume ratio of K3Co(CN)6 to deionized water is 0.13~0.68:100, in g / mL; (2) Preprocessing The MnCo-MOF material is immersed in a mixed aqueous solution of glucose and alkyl glycoside, kept at 70-90° C. for 0.5-1 h, and then dried, wherein the mass percentage concentration of glucose in the mixed aqueous solution is 20-40%, and the mass ratio of glucose to alkyl glycoside is 4:0.5-1; (3) Selenization treatment The pretreated MnCo-MOF material and selenium powder were placed in a tubular furnace, with the selenium powder upstream and the MnCo-MOF material downstream. Under an argon atmosphere, the temperature was raised to 400-450°C at a rate of 2-5°C / min and kept warm for 1.5-2.5h. During this process, the argon flow rate was 45-60sccm. Then the temperature was continued to be raised to 550-600°C and kept warm for 0.5-1h. During this process, the argon flow rate was 30-40sccm to obtain a MnSe2 / CoSe2 / C composite material.
[0019] A lithium-ion battery electrode material, characterized in that: the electrode material is a composite material composed of cubic selenide and carbon, the carbon material is coated on the surface of the bimetallic selenide, and the composite material is a MnSe2 / CoSe2 / C composite material obtained by pre-treating the MnCo-MOF material as a precursor and then performing selenization treatment.
[0020] Furthermore, the MnCo-MOF material is prepared by dissolving Mn(CH3COO)2·4H2O and PVP-K30 in a mixed solvent consisting of anhydrous ethanol and deionized water to obtain solution A, and dissolving K3Co(CN)6 in deionized water to obtain solution B. Solution A and solution B are mixed and aged at room temperature to obtain MnCo-MOF.
[0021] Furthermore, in the solution A, the mass ratio of Mn(CH3COO)2·4H2O and PVP-K30 is 0.22~0.44:0.75~3, the mass volume ratio of Mn(CH3COO)2·4H2O and the mixed solvent is 0.1~0.5:100, in g / mL, and the volume ratio of anhydrous ethanol to deionized water is 2:1.
[0022] Furthermore, in the solution B, the mass volume ratio of K3Co(CN)6 and deionized water is 0.13~0.68:100, in g / mL.
[0023] Furthermore, the solution A and the solution B are mixed in a molar ratio of Mn to Co of 1.2 to 1.8:1 and aged at room temperature for 15 to 26 hours.
[0024] Furthermore, the pretreatment is to immerse the MnCo-MOF material in a mixed aqueous solution of glucose and alkyl glycoside, keep it warm at 70-90°C for 0.5-1h, and then dry it. The mass percentage concentration of glucose in the mixed aqueous solution is 20-40%, and the mass ratio of glucose to alkyl glycoside is 4:0.5-1.
[0025] Furthermore, the selenization treatment is to place the pretreated MnCo-MOF material and selenium powder in a tubular furnace, with the selenium powder at the upstream and the MnCo-MOF material at the downstream, and heat to 400-450°C at a rate of 2-5°C / min under an argon atmosphere, and keep warm for 1.5-2.5 hours. During this process, the argon flow rate is 45-60 sccm, and then continue to heat to 550-600°C, and continue to keep warm for 0.5-1 hour. During this process, the argon flow rate is 30-40 sccm.
[0026] The present invention has the following technical effects: The MnSe2 / CoSe2 / C composite material of the present invention has a uniform cubic structure, uniform morphology, uniform size, excellent dispersibility, high purity, and purity up to 99.3%. The carbon layer forms a complete coating on the bimetallic selenide. It has excellent electrical conductivity and cycle stability, and can be effectively applied to new energy vehicles as a negative electrode material for lithium-ion batteries of vehicles.
[0027] The preparation method of the present invention solves the problems of easy collapse of the cubic structure and poor structural stability during the selenization process, the problem of more impurities during the refinement process, and the problem of poor coating performance of bimetallic selenide of the cubic structure of carbon materials and easy agglomeration. The carbon-based electrode material prepared by the present invention has excellent structural stability and is in a uniformly dispersed cubic shape. The carbon layer completely coats the bimetallic selenide, effectively alleviating the volume expansion effect. The purity of the composite material is as high as 99.3%. When the carbon-based electrode material is used as a negative electrode material for a lithium-ion battery of a new energy vehicle, it has excellent lithium storage performance and cycle stability. At 100 mA g -1 After 200 charge and discharge cycles at a current density of 1.34 W, the discharge capacity is 662 mAh g -1 The charging and discharging performance is stable during the cycle, and there will be no current fluctuations. The cycle life is long. During 1,000 cycles, the performance has not decayed, which broadens the choice range for improving the endurance of new energy vehicles. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 : XRD pattern of the cubic MnSe2 / CoSe2 / C composite material prepared in Example 1 of the present invention.
[0029] Figure 2 : SEM image of the cubic MnSe2 / CoSe2 / C composite material prepared in Example 1 of the present invention.
[0030] Figure 3 : TEM image of the cubic MnSe2 / CoSe2 / C composite material prepared in Example 1 of the present invention.
[0031] Figure 4: SEM images of the composite materials prepared in each comparative example.
[0032] Figure 5 : Raman image of the cubic MnSe2 / CoSe2 / C composite material prepared in Example 1 of the present invention.
[0033] Figure 6 : TGA diagram of the cubic MnSe2 / CoSe2 / C composite material prepared in Example 1 of the present invention.
[0034] Figure 7 : CV diagram of the cubic MnSe2 / CoSe2 / C composite material prepared in Example 1 of the present invention.
[0035] Figure 8 : EIS graph of the cubic MnSe2 / CoSe2 / C composite material prepared in Example 1 of the present invention.
[0036] Fig. 9 : Charge and discharge cycle diagram of the cubic MnSe2 / CoSe2 / C composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.
[0038] Example 1 A method for preparing a lithium ion battery electrode material comprises the following steps: (1) Synthesis of MnCo-MOF materials Mn(CH3COO)2·4H2O and PVP-K30 were dissolved in a mixed solvent of anhydrous ethanol and deionized water to obtain solution A, K3Co(CN)6 was dissolved in deionized water to obtain solution B, solution A and solution B were mixed at a molar ratio of Mn to Co of 1.5:1 and aged at room temperature for 20 h, the precipitate was collected by centrifugation, washed with ethanol and deionized water in sequence, and then dried to obtain MnCo-MOF, wherein in solution A, the mass ratio of Mn(CH3COO)2·4H2O to PVP-K30 was 0.40:0.75~3, the mass volume ratio of Mn(CH3COO)2·4H2O to the mixed solvent was 0.1~0.5:100, in g / mL, the volume ratio of anhydrous ethanol to deionized water was 2:1, and in solution B, the mass volume ratio of K3Co(CN)6 to deionized water was 0.13~0.68:100, in g / mL; (2) Preprocessing The MnCo-MOF material is immersed in a mixed aqueous solution of glucose and alkyl glycoside, kept at 70-90° C. for 0.5-1 h, and then dried, wherein the mass percentage concentration of glucose in the mixed aqueous solution is 30%, and the mass ratio of glucose to alkyl glycoside is 4:0.5-1; (3) Selenization treatment The pretreated MnCo-MOF material and selenium powder were placed in a tubular furnace, with the selenium powder upstream and the MnCo-MOF material downstream. Under an argon atmosphere, the temperature was raised to 420°C at a rate of 5°C / min and kept for 2 hours. The argon flow rate was 50 sccm during the process. The temperature was then raised to 580°C and kept for 0.5 hours. The argon flow rate was 35 sccm during the process. MnSe2 / CoSe2 / C composite material was obtained.
[0039] Figure 1 From the XRD diagram of the MnSe2 / CoSe2 / C composite material prepared in this embodiment, it can be seen that the prepared composite material has obvious characteristic peaks and high purity. After calculation, the purity of the MnSe2 / CoSe2 / C composite material reaches 99.3%, the impurity content is low, and the yield also reaches 77.8%.
[0040] Figure 2 and Figure 3 The scanning electron microscope image and transmission electron microscope image of the MnSe2 / CoSe2 / C composite material prepared in this embodiment are respectively Figure 2 It can be seen that the composite material is uniformly dispersed, with a regular cubic structure, uniform structural size, and a densely coated carbon layer evenly attached to the surface, making the surface of the material present a uniform rough structure. Figure 3 It can be observed that a uniform carbon layer forms a complete coating on the surface of the bimetallic selenide.
[0041] Figure 5 This is the Raman image of the MnSe2 / CoSe2 / C composite material prepared in this embodiment. The ratio of the intensity of the D peak and the G peak, i.e., ID / IG, ID / IG is greater than 1, indicating that the disordered carbon content in the MnSe2 / CoSe2 / C composite material is dominant, which is more conducive to the storage of lithium ions.
[0042] Figure 6 is the TGA graph of the MnSe2 / CoSe2 / C composite material prepared in this example. o There are two steps of continuous mass loss in the MnSe2 / CoSe2 / C composites within the C range. These mass losses are caused by the combustion of carbon in air.
[0043] Figure 7This is the CV graph of the MnSe2 / CoSe2 / C composite material prepared in this example. The 2nd and 3rd CV graphs have good overlap, indicating that the MnSe2 / CoSe2 / C composite material has high reversibility for lithiation / delithiation reactions.
[0044] The MnSe2 / CoSe2 / C composite material prepared in this embodiment well maintains the cubic morphology of the binary metal organic framework compound, has high crystallinity, high specific surface area and porosity, and exhibits excellent lithium storage performance, large storage capacity, long cycle life, and can be cycled at least 1000 times without performance degradation. It has good stability during use and will not experience current fluctuations. Fig. 9 As shown, at 100 mA g -1 After 200 charge and discharge cycles at a current density of 1.5 %, the discharge capacity still reached 662 mAh g -1 . As a new energy vehicle, lithium-ion batteries have excellent lithium storage performance and charge and discharge cycle stability.
[0045] Comparative Example 1 Compared with Example 1, the difference is that the selenization steps of the pretreated MnCo-MOF material are as follows: The pretreated MnCo-MOF material and selenium powder were placed in a tubular furnace, with the selenium powder upstream and the MnCo-MOF material downstream. Under an argon atmosphere, the temperature was raised to 420°C at a rate of 5°C / min and kept for 2 hours. During this process, the argon flow rate was 35sccm. Then the temperature was continued to be raised to 580°C and kept for 0.5 hours. During this process, the argon flow rate was 50sccm, and a MnSe2 / CoSe2 / C composite material was obtained.
[0046] Comparative Example 2 Compared with Example 1, the MnCo-MOF material was prepared according to the method in Example 1. When the MnCo-MOF material was pretreated, the soaking solution used was a glucose aqueous solution with a mass percentage concentration of 30%, and then the selenium powder was directly subjected to the same selenization treatment as in Example 1.
[0047] Blank group: Compared with Example 1, the MnCo-MOF material is directly selenized without pretreatment. The selenization step is that the MnCo-MOF material and selenium powder are placed in a tubular furnace, with the selenium powder at the upstream and the MnCo-MOF material at the downstream. Under an argon atmosphere, the temperature is raised to 580°C at a rate of 5°C / min, and the temperature is kept at a high temperature for 2.5 hours. During the process, the argon gas flow rate is 50sccm, and a MnSe2 / CoSe2 / C composite material is obtained.
[0048] The scanning electron microscope images of the composite materials prepared by each comparison are as follows: Figure 4As shown, it can be seen from the electron micrographs of the products of Comparative Example 1 (a), Comparative Example 2 (b) and the blank group (c) that only pretreatment was performed in Comparative Example 1, and because the argon gas flow rate of the two-step selenization was adjusted during the selenization process, although the cubic structure was more retained, the carbon material was not well coated on its surface, but formed a bond between the cubic particles. In Comparative Example 2, in the absence of the addition of alkyl glycosides during the pretreatment, the prepared product was completely unable to maintain the cubic structure, and other morphological structures were formed. In the blank group, the structure collapsed and the morphology was more messy. After detection and calculation, the purity of the composite materials prepared in Comparative Example 1, Comparative Example 2 and the blank group was 81.9%, 95.6% and 76.3%, respectively.
[0049] In long-term experiments, we also tried to adjust the molar ratio of Mn and Co in the MnCo-MOF material and found that the prepared MOF materials can basically be prepared into a cubic uniform structure, which can be used as a template for the subsequent preparation of composite materials. However, the molar ratio of Mn and Co will lead to the proportion of Mn-based selenide and Co-based selenide in the subsequent prepared MnSe2 / CoSe2 / C composite material, thereby affecting its lithium storage performance. We found that when other conditions remain unchanged, when the molar ratio of Mn and Co is 1.2~1.8:1, the prepared MnSe2 / CoSe2 / C composite material has the best lithium storage performance.
[0050] Example 2 A method for preparing a lithium ion battery electrode material comprises the following steps: (1) Synthesis of MnCo-MOF materials Mn(CH3COO)2·4H2O and PVP-K30 were dissolved in a mixed solvent of anhydrous ethanol and deionized water to obtain solution A, K3Co(CN)6 was dissolved in deionized water to obtain solution B, solution A and solution B were mixed according to a molar ratio of Mn to Co of 1.2:1, aged at room temperature for 26 hours, centrifuged to collect the precipitate, washed with ethanol and deionized water in turn, and then dried to obtain MnCo-MOF, wherein in solution A, the mass ratio of Mn(CH3COO)2·4H2O to PVP-K30 was 0.44:3, the mass volume ratio of Mn(CH3COO)2·4H2O to the mixed solvent was 0.5:100, in g / mL, the volume ratio of anhydrous ethanol to deionized water was 2:1, and in solution B, the mass volume ratio of K3Co(CN)6 to deionized water was 0.68:100, in g / mL; (2) Preprocessing The MnCo-MOF material was immersed in a mixed aqueous solution of glucose and alkyl glycoside, kept at 90° C. for 0.5 h, and then dried, wherein the mass percentage concentration of glucose in the mixed aqueous solution was 20%, and the mass ratio of glucose to alkyl glycoside was 4:0.5; (3) Selenization treatment The pretreated MnCo-MOF material and selenium powder were placed in a tubular furnace, with the selenium powder upstream and the MnCo-MOF material downstream. Under an argon atmosphere, the temperature was raised to 450°C at a rate of 3°C / min and kept warm for 1.5 hours. During this process, the argon flow rate was 60 sccm. Then the temperature was continued to be raised to 550°C and kept warm for 1 hour. During this process, the argon flow rate was 40 sccm, and a MnSe2 / CoSe2 / C composite material was obtained.
[0051] The MnSe2 / CoSe2 / C composite material prepared in this example has a uniform cubic structure, uniform size and high purity. The purity of the MnSe2 / CoSe2 / C composite material is calculated to be 99.1%. When the material is used as an electrode material for an ion battery, the -1 After 200 charge and discharge cycles at a current density of 1.5 %, the discharge capacity still reached 647 mAh g -1 As a new energy vehicle, lithium-ion batteries have excellent lithium storage performance and charge and discharge cycle stability.
[0052] Example 3 A method for preparing a lithium ion battery electrode material comprises the following steps: (1) Synthesis of MnCo-MOF materials Mn(CH3COO)2·4H2O and PVP-K30 were dissolved in a mixed solvent of anhydrous ethanol and deionized water to obtain solution A, K3Co(CN)6 was dissolved in deionized water to obtain solution B, solution A and solution B were mixed according to a molar ratio of Mn to Co of 1.8:1, aged at room temperature for 15 hours, centrifuged to collect the precipitate, washed with ethanol and deionized water in turn, and then dried to obtain MnCo-MOF, wherein in solution A, the mass ratio of Mn(CH3COO)2·4H2O to PVP-K30 was 0.22:0.75, the mass volume ratio of Mn(CH3COO)2·4H2O to the mixed solvent was 0.1:100, in g / mL, the volume ratio of anhydrous ethanol to deionized water was 2:1, and in solution B, the mass volume ratio of K3Co(CN)6 to deionized water was 0.13:100, in g / mL; (2) Preprocessing The MnCo-MOF material was immersed in a mixed aqueous solution of glucose and alkyl glycoside, kept at 70° C. for 1 hour, and then dried, wherein the mass percentage concentration of glucose in the mixed aqueous solution was 40%, and the mass ratio of glucose to alkyl glycoside was 4:1; (3) Selenization treatment The pretreated MnCo-MOF material and selenium powder were placed in a tubular furnace, with the selenium powder upstream and the MnCo-MOF material downstream. Under an argon atmosphere, the temperature was raised to 450°C at a rate of 2°C / min and kept warm for 2.5 hours. During this process, the argon flow rate was 45 sccm. Then the temperature was continued to be raised to 600°C and kept warm for 0.5~1 hour. During this process, the argon flow rate was 30 sccm, and a MnSe2 / CoSe2 / C composite material was obtained.
[0053] The MnSe2 / CoSe2 / C composite material prepared in this embodiment has a uniform cubic structure, uniform size and high purity. The purity of the MnSe2 / CoSe2 / C composite material is calculated to be 99.2%. When the material is used as an electrode material for lithium-ion batteries, it can be used at 100 mA g -1 After 200 charge and discharge cycles at a current density of 1.5 %, the discharge capacity still reached 637 mAh g -1 As a new energy vehicle, lithium-ion batteries have excellent lithium storage performance and charge and discharge cycle stability.
Claims
1. A method for preparing a lithium ion battery electrode material, characterized in that: The method comprises the steps of preparing MOF material, pretreatment of MOF material and selenization treatment. The MOF material pretreatment is to immerse the MOF material in a mixed aqueous solution of glucose and alkyl glycoside, keep the mixture at 70-90°C for 0.5-1h, and then dry the mixture. The mass percentage concentration of glucose in the mixed aqueous solution is 20-40%, and the mass ratio of glucose to alkyl glycoside is 4:0.5-1.
2. The method for preparing a lithium ion battery electrode material according to claim 1, characterized in that: The selenization treatment is to place the pretreated MOF material and selenium powder in a tubular furnace, with the selenium powder at the upstream and the MOF material at the downstream, and heat to 400-450°C at a rate of 2-5°C / min under an argon atmosphere, and keep warm for 1-1.5 hours. During this process, the argon flow rate is 45-60 sccm, and then continue to heat to 550-600°C, and continue to keep warm for 1-2.5 hours. During this process, the argon flow rate is 30-40 sccm.
3. A method for preparing a lithium ion battery electrode material according to claim 1 or 2, characterized in that: The MOF material is prepared by dissolving Mn(CH3COO)2·4H2O and PVP-K30 in a mixed solvent consisting of anhydrous ethanol and deionized water to obtain solution A, dissolving K3Co(CN)6 in deionized water to obtain solution B, and mixing solution A and solution B and aging at room temperature to obtain MnCo-MOF material.
4. A method for preparing a lithium ion battery electrode material according to any one of claims 1 to 3, characterized in that: In the solution A, the mass ratio of Mn(CH3COO)2·4H2O and PVP-K30 is 0.22~0.44:0.75~3, the mass volume ratio of Mn(CH3COO)2·4H2O and the mixed solvent is 0.1~0.5:100, in g / mL, and the volume ratio of anhydrous ethanol to deionized water is 2:
1.
5. The method for preparing a lithium ion battery electrode material according to claim 4, characterized in that: In the solution B, the mass volume ratio of K3Co(CN)6 and deionized water is 0.13~0.68:100, and the unit is g / mL.
6. A method for preparing a lithium ion battery electrode material, characterized in that: The steps include: (1) Synthesis of MnCo-MOF materials Mn(CH3COO)2·4H2O and PVP-K30 were dissolved in a mixed solvent consisting of anhydrous ethanol and deionized water to obtain solution A, and K3Co(CN)6 was dissolved in deionized water to obtain solution B. Solution A and solution B were mixed according to a molar ratio of Mn to Co of 1.2 to 1.8:1, aged at room temperature for 15 to 26 hours, and the precipitate was collected by centrifugation, washed with ethanol and deionized water in turn, and then dried to obtain MnCo-MOF. In the solution A, The mass ratio of Mn(CH3COO)2·4H2O to PVP-K30 is 0.22~0.44:0.75~3, the mass volume ratio of Mn(CH3COO)2·4H2O to the mixed solvent is 0.1~0.5:100, in g / mL, the volume ratio of anhydrous ethanol to deionized water is 2:1, and in the solution B, the mass volume ratio of K3Co(CN)6 to deionized water is 0.13~0.68:100, in g / mL; (2) Preprocessing The MnCo-MOF material is immersed in a mixed aqueous solution of glucose and alkyl glycoside, kept at 70-90° C. for 0.5-1 h, and then dried, wherein the mass percentage concentration of glucose in the mixed aqueous solution is 20-40%, and the mass ratio of glucose to alkyl glycoside is 4:0.5-1; (3) Selenization treatment The pretreated MnCo-MOF material and selenium powder were placed in a tubular furnace, with the selenium powder upstream and the MnCo-MOF material downstream. Under an argon atmosphere, the temperature was raised to 400-450°C at a rate of 2-5°C / min and kept warm for 1-1.5 h. During this process, the argon flow rate was 45-60 sccm. The temperature was then continued to be raised to 550-600°C and kept warm for 1-2.5 h. During this process, the argon flow rate was 30-40 sccm to obtain a MnSe2 / CoSe2 / C composite material.
7. A lithium ion battery electrode material, characterized in that: The electrode material is a cubic MnSe2 / CoSe2 / C composite material, in which a carbon material is coated on the surface of a bimetallic selenide MnSe2 / CoSe2. The MnSe2 / CoSe2 / C composite material is obtained by using a MnCo-MOF material as a precursor and then undergoing selenization treatment after pretreatment.
8. A lithium ion battery electrode material as claimed in claim 7, characterized in that: The pretreatment is to immerse the MnCo-MOF material in an aqueous solution of glucose and alkyl glycoside, keep it warm at 70-90°C for 0.5-1h, and then dry it. The mass percentage concentration of glucose in the mixed aqueous solution is 20-40%, and the mass ratio of glucose to alkyl glycoside is 4:0.5-1.
9. A lithium ion battery electrode material according to claim 7 or 8, characterized in that: The selenization treatment is to place the pretreated MnCo-MOF material and selenium powder in a tubular furnace, with the selenium powder at the upstream and the MnCo-MOF material at the downstream, and heat to 400-450°C at a rate of 2-5°C / min under an argon atmosphere, and keep warm for 1-1.5 hours. During this process, the argon flow rate is 45-60 sccm, and then continue to heat to 550-600°C, and continue to keep warm for 1-2.5 hours. During this process, the argon flow rate is 30-40 sccm.
Citation Information
Patent Citations
Preparation method for lithium manganese phosphate / graphene / carbon nanocomposite
CN105449178A
Alkali metal phosphate composite electrode material, preparation method thereof and secondary battery
CN116190603A
Macroporous Zn-MOF-PVP in-situ encapsulated beta-glucosidase compound as well as preparation method and application thereof
CN118028282A
Shuttling-free batteries and preparation method thereof
WO2024055059A1
